2003
DOI: 10.1021/es020988s
|View full text |Cite
|
Sign up to set email alerts
|

Organic and Elemental Carbon Measurements during ACE-Asia Suggest a Longer Atmospheric Lifetime for Elemental Carbon

Abstract: During the ACE-Asia intensive field campaign (March 14-April 20, 2001), PM1.0 organic (OC) and elemental carbon (EC) concentrations were measured onboard the NOAA R/V Ronald H. Brown over the Northwest Pacific Ocean using a semi-continuous automated carbon analyzer downstream of a carbon-impregnated filter denuder. This OC and EC measurement achieved a mean time resolution of about 200 min over the Pacific Ocean, substantially lower than that achieved previously (24 h). The semi-continuous measurements, in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
46
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 38 publications
12
46
0
Order By: Relevance
“…Differences in 48-h mean temperature did not help explain the remaining variance (not shown). The sampling artifact findings are consistent with previous outdoor studies in magnitude and functional dependence (Turpin et al, 2000;Lim et al, 2003;Polidori et al, 2006). Clearly, if uncorrected an artifact of this magnitude would result in substantial bias in the reported particulate OC concentrations.…”
Section: Resultssupporting
confidence: 89%
“…Differences in 48-h mean temperature did not help explain the remaining variance (not shown). The sampling artifact findings are consistent with previous outdoor studies in magnitude and functional dependence (Turpin et al, 2000;Lim et al, 2003;Polidori et al, 2006). Clearly, if uncorrected an artifact of this magnitude would result in substantial bias in the reported particulate OC concentrations.…”
Section: Resultssupporting
confidence: 89%
“…The relatively low OC/EC ratios observed in spring, fall, and winter compared to summer suggest a possible longer residence time for EC than OC under long-range transport from the continent. The OC/EC ratios in the present study were higher than those observed in cities of the Pearl River Delta Region, which were between 1.0 and 4.0 in summer (Cao et al, 2004), but comparable to values from observations from other islands (Feng et al, 2007;Simoneit et al, 2004), and a cruise traversing the Northwest Pacific Ocean (Lim et al, 2003, Table 3). …”
Section: Secondary Organic Carbon (Soc)supporting
confidence: 87%
“…These values are quite close to the detection limit for EC for semicontinuous carbon measurements, typically around 0.15-0.35 gC/m 3 (as determined by Lim et al 21 ), and suggest that indoor sources of EC were not an important contributor to measured indoor EC during CHAPS. These outcomes are consistent with I/O EC ratios close to or slightly lower than unity obtained in several previous studies conducted both in California 50,51 and around the world.…”
Section: Infiltration Factor Estimatessupporting
confidence: 86%
“…Carbon data corresponding with time periods affected by rain were not considered in the determination of a and b because of the possibility of differential wet scavenging. 21,23 The average coefficient of determination (R 2 ) for all monthly regressions was 0.87 Ϯ 0.06 (1), which adds confidence to our results.…”
Section: Meansupporting
confidence: 82%